An Analysis of the Influence of Brand Image and Consumer Trust on Customer Loyalty in Food Sector Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta (A Study of College Students in Yogyakarta) - Annisa Hilmia Putri; Eko Prasojo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in the food sector has intensified business competition, particularly in urban areas such as Yogyakarta. In this competitive environment, brand image and consumer trust are considered key factors in building customer loyalty, especially among student consumers who dominate the market segment. This study addresses the problem of whether brand image and consumer trust influence customer loyalty in food-sector MSMEs in Yogyakarta. The objectives of this research are to examine the effect of brand image on customer loyalty and to analyze the effect of consumer trust on customer loyalty in food-sector MSMEs in Yogyakarta.This research employs a quantitative approach. The population consists of student consumers who have purchased food products from MSMEs in Yogyakarta. A purposive sampling technique was used, resulting in 100 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 26. Instrument testing included validity and reliability tests, while classical assumption tests comprised normality, linearity, heteroscedasticity, and multicollinearity tests. Hypothesis testing was conducted using the partial t-test. The results indicate that brand image has a positive and significant effect on customer loyalty. Consumer trust also shows a positive and significant effect on customer loyalty. These findings confirm that a strong brand image and high consumer trust play an important role in increasing customer loyalty toward food-sector MSMEs in Yogyakarta.